A Parallel Path Planning Approach Based on Organic Computing Principles - Schmidt, Michael; Fey, Dietmar (Proc. of the 20th IASTED Intern. Conf. on Parallel and Distributed Computing and Systems, 2008)
Path planning is one of the most computation expensive tasks in the field of mobile robotics especially in dynamically changing environments. It is difficult to meet realtime requirements with serial path planning algorithms. This would require a high speed processor. Particularly in small autonomous robot systems, this is inefficient due to the energy consumption and space requirement. In contrast, we propose a parallel path planning approach based on Marching Pixels which is a new innovative Organic Computing principle. It can be used as coarse global path planner in dynamically changing environments because the algorithm is very fast and only requires few resources.
UnivIS-Import:2015-04-16:Pub.2008.tech.IMMD.IMMD3.aparal
Keywords: Marching pixels; Mobile robotics; Parallel algorithms; Path planning